Effective dose of propolis extract combined with bovine bone graft on the number of osteoblasts and osteoclasts in tooth extraction socket preservation - Teguh Setio Yuli Prabowo; Utari Kresnoadi; Hanoem Eka Hidayati (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Maintaining a good ridge is required during prosthodontic treatment. Hence, adequate alveolar bone support is considered an important factor in pursuing successful dentures. Propolis extract combined with bovine bone graft is a recent and innovative material in the process of socket preservation, as the caffeic acid phenethyl ester (CAPE) it contains can suppress the inflammatory process. Purpose: This study aims to determine the effective dose of propolis extract combined with bovine bone graft on the number of osteoblasts and osteoclasts in socket preservation. Methods: Twenty-eight Cavia cobaya animals were divided into four groups of seven. Group I was given 25 grams of PEG, while Group II were given a propolis extract at a dose of 0.5% combined with bovine bone graft. Group III were given a propolis extract at a dose of 1% combined with bovine bone graft and Group IV were given a propolis extract at a dose of 2% combined with bovine bone graft. On day 30, the lower incisor of each subject was extracted and induced with PEG and propolis (dose 0.5%, 1%, 2%). Histopathological examinations of osteoblasts and osteoclasts were measured with a 400x magnification light microscope. One-way ANOVA and Tukey HSD tests were performed to analyse data statistically. Results: The propolis extract combined with bovine bone graft not only increased the number of osteoblasts but also reduced the number of osteoclasts. The most effective dose for the propolis extract combined with bovine bone graft was 2%. Conclusion: The propolis extract combined with bovine bone graft could be effective in tooth extraction socket preservation at a dose of 2%.